Influencing factors and method of estimating the pattern area designed with recovered yarn from used shaped knitted clothes - Dao, Thi Chinh Thuy; Le, Khanh Trang; Vu, Thi Thuy; Nguyen, Thi Thanh Thao; Tong, Thi Phuong Anh (JST: Engineering And Technology For Sustainable Development, 2025)
Shaped knitted clothes such as sweaters and cardigans are popular and abundant textile products but in the fast fashion trend, their normal life cycle is usually short, about 28 laundry cycles. Therefore, recycling used shaped knitted clothes is of interest to many designers all over the world for a more sustainable environment and development. Sweaters and cardigans are often produced by shaped knitting method. So, an effective recycling process is unravelling continuous yarn from the used clothes to get input for knitting of recycled items. In this way, the longer the length of yarn collected the better, and managing the length of recovered yarn in stock is very important for designers. This study investigated the influence of product construction and knitted structure on the length of continuous yarn unravelling from used shaped knitted clothes. In addition, a method to estimate the pattern area designed from collected yarn was proposed basing on specifications recommended by SDS-One Apex Design system of Shima seiki.